Демаркация позитивной науки и метафизики - Голованов, Борис Дмитриевич (Грамота, 2015)
В статье рассматривается проблема демаркации научного и ненаучного знания, в частности, демаркации науки и идеологии. Автор анализирует варианты решения этой проблемы представителями позитивизма и полагает, что специфика идеологического знания создается включением в идеологические доктрины ценностных суждений и психопрактик, блокирующих критическое мышление индивидов. Мышление, лишенное критичности, может быть привязано к определенной идее и ограниченному историческому опыту и только из него черпать доказательства своей состоятельности, не обращая внимания на противоречащую аргументацию.

The article considers the problem of the demarcation of scientific and non-scientific knowledge, in particular, the demarcation of science and ideology. The author analyzes solutions to this problem proposed by the representatives of positivism and believes that the specificity of ideological knowledge is created by the introduction of value judgments and psycho practices blocking individuals’ critical thinking in ideological doctrines. Thinking, devoid of criticality, can be linked to a particular idea and limited historical experience and can draw the proof of its relevancy from this experience only not paying attention to contradictory argumentation.
Demarcation of positive science and metaphysics
Keywords: метод; критическое мышление; идеология; идея; method; critical thinking; ideology; idea